Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.21767/2472-5056.100030
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Denosumab for the Treatment of Osteoporosis in Patients with Chronic Kidney Disease

Abstract: Background: Chronic kidney disease (CKD) is an independent risk factor for osteoporosis and may lead to metabolic abnormalities that accelerate bone loss. Bisphosphonates, the most widely used treatment for osteoporosis, are contraindicated in patients with severe renal impairment. In the present study, we assessed whether denosumab is a safe and effective treatment for osteoporosis in patients with CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(27 reference statements)
1
2
1
Order By: Relevance
“…Unfortunately, our study revealed that treatment with denosumab for a mean of 19.135±16.218 months duration in HD patients with osteoporosis was not associated with an increase in the BMD of the spine, and hope that serum ALP levels decreased in HD patients after treatment with denosumab but was no statistically significant difference when compared with before treatment. Our results regarding BMD are not in agreement with many previous studies as Hiramatsu et al (21) and Suzuki et al (22) revealed that denosumab is an applicable treatment for osteoporosis in patients with CKD. The explanation of our negative results regarding the efficacy of denosumab treatment for osteoporosis is that all our studied patients were on HD and regular HD may affect the pharmacokinetics and pharmacodynamics of denosumab.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, our study revealed that treatment with denosumab for a mean of 19.135±16.218 months duration in HD patients with osteoporosis was not associated with an increase in the BMD of the spine, and hope that serum ALP levels decreased in HD patients after treatment with denosumab but was no statistically significant difference when compared with before treatment. Our results regarding BMD are not in agreement with many previous studies as Hiramatsu et al (21) and Suzuki et al (22) revealed that denosumab is an applicable treatment for osteoporosis in patients with CKD. The explanation of our negative results regarding the efficacy of denosumab treatment for osteoporosis is that all our studied patients were on HD and regular HD may affect the pharmacokinetics and pharmacodynamics of denosumab.…”
Section: Discussioncontrasting
confidence: 99%
“…A dose of 1.0 to 1.5 μg/day of vitamin D was required to keep serum calcium during treatment with denosumab and monitoring of serum calcium is important. Our results regarding the adverse effect of denosumab treatment are in agreement with the study of Hiramatsu et al (21), Suzuki et al (22), and Ullah et al (23) who revealed hypocalcemia was a common complication of denosumab treatment particularly in HD patients. the administration of denosumab in patients with high bone turnover creates a situation similar to "hungry bone syndrome (24) leading to a sudden influx of calcium into the bone necessary for bone mineralization and remodeling.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, routine monitoring of kidney function is advised particularly among patients who are concurrently using other medications that impact kidney function [34][35][36][37] . The pharmacokinetics and pharmacodynamics of denosumab used at the standard dose, are unaffected by the presence of renal impairment 38 . In fact, among patients with chronic kidney disease, denosumab provides greater bone mineral density (BMD) gains than bisphosphonates, although vitamin D supplementation is required to prevent hypocalcemia among denosumab users in this population 38 .…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetics and pharmacodynamics of denosumab used at the standard dose, are unaffected by the presence of renal impairment 38 . In fact, among patients with chronic kidney disease, denosumab provides greater bone mineral density (BMD) gains than bisphosphonates, although vitamin D supplementation is required to prevent hypocalcemia among denosumab users in this population 38 . Impaired renal function, which becomes more common with advancing age, increases the risk of progressive bone loss and osteoporosis.…”
Section: Discussionmentioning
confidence: 99%